2021
DOI: 10.1093/jalm/jfaa221
|View full text |Cite
|
Sign up to set email alerts
|

Capillary Blood Levels of Hydroxychloroquine and Methotrexate Are Stable for up to 5 Years When Collected on Volumetric Absorptive Microsamplers

Abstract: Background Hydroxychloroquine (HCQ) and methotrexate (MTX) are common antirheumatic drugs used chronically by patients with systemic lupus erythematosus (SLE) and rheumatoid arthritis (RA) (1, 2). Therapeutic drug monitoring (TDM) of HCQ and MTX provides critical compliance information, but typically requires venipuncture and shipment of refrigerated blood samples to the clinical laboratory. Capillary blood collection by finger prick offers a convenient alternative to venipuncture. The long-t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 21 publications
0
1
0
Order By: Relevance
“…The patients in that study reported a more successful collection experience compared with DBS cards, where 20% of the cards were unable to be completely filled [ 49 ]. The same research team also has recently reported that the drug HCQ remains stable on Mitra devices for up to 5 years [ 50 ]. Due to the prior success in measuring samples from Mitra, as part of the COVID-19 HCQ prophylactic trial, blood measurements were taken from healthcare workers using Mitra devices [ 51 ].…”
Section: Using Vams In Covid-19 Clinical Trialsmentioning
confidence: 99%
“…The patients in that study reported a more successful collection experience compared with DBS cards, where 20% of the cards were unable to be completely filled [ 49 ]. The same research team also has recently reported that the drug HCQ remains stable on Mitra devices for up to 5 years [ 50 ]. Due to the prior success in measuring samples from Mitra, as part of the COVID-19 HCQ prophylactic trial, blood measurements were taken from healthcare workers using Mitra devices [ 51 ].…”
Section: Using Vams In Covid-19 Clinical Trialsmentioning
confidence: 99%